Durabilitas Campuran Laston Lapis Antara Menggunakan Agregat Sungai Salassa Kabupaten Toraja Utara - Caraka Jaya Gusta Salempa; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The purpose of this study was to determine the effect of immersion variations on the Durability of Intermediate Laston Mixtures. The methodology in this research is to design the specimens using Salassa River aggregate with a composition of 5.00% asphalt content with variations of immersion 0.5 hours, 24 hours, 48 hours, 72 hours, 96 hours. Marshall Immersion Test to get the Durability value due to variations in immersion The results showed that the durability of the asphalt mixture will decrease if it is submerged in water for too long and changes in temperature. Stability of the mixture will decrease if it is submerged in water for too long. The greatest stability is 1394.17 Kg, which means it meets the minimum specification standard of 800 kg. The flow of the asphalt mixture will change its plastic shape due to prolonged immersion. The largest flow value is 2.70. Flow on the asphalt mixture meets the standard specifications of 2-4 mm. The durability value for various immersions in the mixture of Laston Lapis Antara was the largest at 97.44% at 24 hour immersion, the smallest value at 80.62%. The limit of immersion tolerance is 48 hours with a value of 94.59%.